Information needs of post myocardial infarction (MI) patients: nurse’s perception in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) - Ho SE,; Hayati Y,; Ting CK,; Oteh M,; Choy YC, (Penerbit UKM, 2008)
Patient education has been considered as an integral component of care for patient after myocardial infarction. Post myocardial infarction patients require information and knowledge related to their conditions to reduce anxiety and aid recovery. The objective of this study was to identify nurses’ perception on information needs of post MI patients of UKMMC. A cross sectional study using Cardiac Patient Learning Needs Inventory (CPLNI) adopted from Timmins and Kalizer (2002) was used. It comprises seven cate-gories: related to anatomy and physiology, psychological factor, life style factor, medi-cation information, dietary information, physical activity, and symptom management. This study was conducted in coronary care unit (CCU), coronary rehabilitation ward (CRW), medical ward 1 and medical ward 2 from January 2007 to March 2007. 56 res-pondents (96%) who fulfilled the inclusion criteria were recruited in this study. Results showed that CCU and CRW respondents ranked symptom management as their first ranking followed by medication, life style factor, anatomy and physiology, dietary in-formation, physical activity and psychological factor. However, respondents in Medical Ward 1 and 2 reported and ranked medication information as their top priorities fol-lowed by symptom management, psychological factors, dietary information, physical activity, anatomy and physiology and life style factor. There were significant differ-ences between ward nurses’ responses with their perception related to anatomy and physiology, psychology factor, life style factor, physical activity, and symptom man-agement with p value<0.05. This study concluded that the information needs are not always perceived in unison by nursing personnel as the CCU and CRW nurses ranked symptoms management as the cardinal factor whilst Medical Ward 1 and 2 nurses give paramount importance to medication. In order to improve this situation for post MI pa-tient, information need has to be tailored, individualized and prioritized based upon their needs